New Cattleya orchid hybrid - Alves,Guilherme Augusto Cito (2018)
ABSTRACT The hybrid, obtained by back crossing between (Cattleya labiata x Cattleya forbesii) x Cattleya labiata is a vigorous plant, bi-or unifoliate, features slender and cylindrical pseudobulbs and leathery dark-greenish leaves, with oblanceolate shape format of blunt tips with the first flowering four years after sowing. In Londrina, flowering occurred twice a year, between the months of April and May and October and November with 2-4 flowers per pseudobulb and durability ranging from 15 to 20 days. The flowers of the new hybrid were purple with a labellum with a yellow center and purple stripes.